THE INFLUENCE OF IMAGE, PATIENT SATISFACTION AND SERVICE QUALITY ON PATIENT LOYALTY AT JEUMPA HOSPITAL BIREUEN DISTRICT - Zahara Fonna; Halida Bahri; Heriyana; Munandar (RADJA PUBLIKA, 2024)
This research aims to analyze the influence of image, patient satisfaction and service quality on patient loyalty at Jeumpa Hospital, Bireuen Regency . The problem in this research is that there are still many patients who do not have a good level of loyalty to the hospital, this is because many patients complain about very slow service, unfriendly employees and doctor visiting hours that do not comply with hospital regulations and attendance. doctors who sometimes don't care about patient complaints. The method used is a quantitative method with a primary data approach. The number of respondents was 140 patients . The instruments in this research use validity, reliability, classical assumption tests such as normality tests, heteroscedasticity tests, multicollinearity tests. This research was conducted on inpatients at Jeumpa Hospital. In this study, data was obtained from the results of distributing questionnaires directly to respondents who were found at Jeumpa Hospital and those who were close to the Jeumpa Hospital location. The data analysis technique used is multiple linear regression analysis with the help of SPSS. The research results show that the image variable has a positive and significant effect on patient loyalty at Jeumpa Hospital, Bireuen Regency. The patient satisfaction variable has a positive and significant effect on patient loyalty at Jeumpa Hospital, Bireuen Regency. The service quality variable has a negative and insignificant effect on patient loyalty at Jeumpa Hospital, Bireuen Regency .